Validation of an Inquiry Collaborative Tutorial-Based Blended Learning Model and its Supporting Materials to Improve Physics Problem-Solving Skills - Lovy Herayanti; Wahono Widodo; Endang Susantini (Indonesian Publication Center, 2024)
This research aimed to develop and validate an inquiry collaborative tutorial-based blended learning model and its supporting materials to enhance physics problem-solving skills in college students. The study employed a 4-D development model consisting of define, design, develop, and disseminate stages. Validation of the model and learning materials was conducted by experts through Focus Group Discussions (FGD) using expert panel techniques. The results indicated that the developed model and learning materials met the criteria for content and construct validity and demonstrated high reliability. The resulting learning model is expected to provide an alternative for lecturers in overcoming the challenges of online learning and improving students' problem-solving abilities.